2018
DOI: 10.1016/j.contraception.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Medical abortion can be provided safely and effectively by pharmacy workers trained within a harm reduction framework: Nepal

Abstract: The role of pharmacy workers as providers of correct and complete information on safe and effective use of MA needs to be recognized and policies formulated to allow them to provide MA drugs for first trimester use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…In Nepal too, as the study by Tamang et al in this Special Edition shows, the majority of women who went straight to a pharmacy for MA pills to use at home were less than 6 weeks pregnant (70%) and a further 27% were less than 10 weeks. None of the women in that study had complications with pill use [6]. Moreover, as shown in the systematic review undertaken by Kapp et al for this Special Edition existing research "supports the use of medical abortion at gestational ages b42 days".…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In Nepal too, as the study by Tamang et al in this Special Edition shows, the majority of women who went straight to a pharmacy for MA pills to use at home were less than 6 weeks pregnant (70%) and a further 27% were less than 10 weeks. None of the women in that study had complications with pill use [6]. Moreover, as shown in the systematic review undertaken by Kapp et al for this Special Edition existing research "supports the use of medical abortion at gestational ages b42 days".…”
mentioning
confidence: 64%
“…Medical abortion in optimal conditions means that the role of obstetrician-gynecologists can effectively disappear from abortion care, with the exception of complicated pregnancies. They can be replaced by trained midwives and nurses, family planning providers and pharmacy workers after a simple training course, as the papers in this Special Edition from Nepal by Tamang et al [6] and Kyrgyzstan by Johnson et al show is possible [10]. Such research confirms that WHO's 2015 guidelines on allowing trained mid-level providers to manage almost all abortions [11] actually work in practice and should be implemented universally.…”
mentioning
confidence: 81%
“…Comparable results have also been reported from eastern Democratic Republic of Congo where only 18% of women sought abortion care from a physician, nurse or midwife [ 17 ]. These results may speak to the growing body of literature that many women may choose to access oral abortifacients from pharmacies [ 18 ] and to terminate pregnancies with little health care intervention [ 19 ]. However, the DHS data did not specifically report on pharmacies and this is an area that should be considered for future study.…”
Section: Discussionmentioning
confidence: 95%
“…While these studies document that pharmacists are more willing to discuss and provide reproductive health services, such as emergency contraception and condoms, and refer their customers to appropriate care following the intervention, none are able to assess longer‐term impact of their interventions on pharmacist behaviours or on client‐related reproductive health outcomes . A recent intervention in Nepal found that pharmacists trained in MA provided safe and satisfactory care, which was sustained for about 5 years …”
Section: Introductionmentioning
confidence: 99%
“…4 A recent intervention in Nepal found that pharmacists trained in MA provided safe and satisfactory care, which was sustained for about 5 years. 17 Given the increasing evidence that pharmacies are the first and primary point of contact for 11.5 million MA users in India, coupled with the clear dearth in tested pharmacist-based interventions to improve the quality of MA care, our team developed a simple informational and graphic handout (infographic) with information on MA dosing, timing, expected symptoms, side effects, and when to seek care. In India, MA is most commonly purchased and taken through a combination pack ("combi-packs") of one mifepristone (200 mg) and four misoprostol tablets (200 mcg each), thus two types of medication to be taken with specified time spacing must be explained.…”
mentioning
confidence: 99%